Multi-level natural resources governance based on local community: A case study on semi-natural grassland in Tarōji, Nara, Japan - Daisaku Shimada (International Journal of the Commons, 2015)
Japan is facing a bio-diversity crisis as a result of rapid industrialisation. The Japanese Ministry of the Environment formulated a National Biodiversity Strategy based on the Convention on Biological Diversity signed at the Earth Summit in 1992. After an amendment in 2002, the National Biodiversity Strategy addressed three crises in biodiversity: over-exploitation and development that destroys habitats, underutilisation (the 'satoyama' problem) and artificially introduced factors (chemicals, alien species and so on). This paper focuses on the second problem. Secondary natural environments called 'satoyama' have been created and maintained over the centuries by human activity. Because natural environments in Japan have been affected by human-induced disturbances for 35,000 years, many species have evolved in response to these disturbances. If the human activities cease, many of the species that have evolved to survive in managed environments become threatened. Many 'satoyama' have been managed as commonage or common lands, called 'iriai' in Japan. One natural resource system created by commoners is semi-natural grassland, and economic modernisation has led to abandonment of traditional management practices on these grasslands – one of the more evident changes in Japanese 'iriai' practices. Before industrialisation, semi-natural grasslands were managed as a source of green manure, as a harvest for roofing materials (thatch) and as pasture for animals. After industrialisation, however, introduction of chemical fertilizers, changes in building practices and importation of animal feeds rapidly decreased the use value of these grasslands for local residents. On the other hand, their value as public goods – as historical, cultural landscapes and places of biodiversity – which concern a much broader population than the local community – became relatively more important. The resulting problem is how to manage this resource with its new value for new beneficiaries. This paper examines the multi-level management of a semi-natural grassland at Tarōji, in Soni village, in Nara prefecture. In Soni village, members of the local community provide key management input, while local government at the village and prefecture levels share management costs.